Registros nuevos de arañas para el estado de Baja California, México - Jiménez, Ma. Luisa; Palacios-Cardiel, Carlos (Instituto de Ecología, A.C., 2012)
We provide information of ten new records of spiders for the state of Baja California: Xysticus californicus, X. pearcei, Tmarus angulatus and Habronattus oregonensis are new records for Mexico; Mecaphesa californica, Hibana cambridgei, Thiodina hespera and Oxyopes scalaris are new records for Baja California. Xysticus locuples and Titanebo mexicanus are reconfirmed species for this region. To the date we confirm the presence of 208 species for the state.